Summary of 2018 ESC Guidelines on definition of myocardial infarction, myocardial revascularisation, cardiovascular disease during pregnancy and on arterial hypertension. Issue 3 (3rd May 2020) - Claeys, Marc J.; Coussement, Patrick; Pasquet, Agnes; De Backer, Tine; De Pauw, Michel
Abstract: During the ESC congress in September 2018 in Munich, the new ESC guidelines were presented and are now available on the ESC website. The new guidelines describe the definition of myocardial infarction and covers management recommendations on following cardiovascular items: myocardial revascularisaton, cardiovascular disease during pregnancy and arterial hypertension. The present document gives a summary of these guidelines and highlights the most important recommendations and changes in the management of these diseases. It will help to increase awareness about the new guidelines and may stimulate to consult the full document for specific items. Ultimately, the authors hope that this document will enhance the implementation of new ESC guidelines in daily clinical practice.